2009
DOI: 10.1002/jez.563
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar binding of an anti‐NMDA receptor antibody in hydra: a non‐canonical role for an NMDA receptor protein?

Abstract: Two emerging concepts in cell biology are the back-and-forth trafficking of receptor proteins and nuclear transcription factors between the nucleus and the cell membrane, and the alternative splicing of messenger RNA to produce similar proteins targeted to different cell sites. Recent evidence suggests that the nucleolus is a dynamic structure whose components may be involved in both types of trafficking. In the nervous system of higher animals, the N-methyl-D-aspartate (NMDA)-specific glutamate receptor has v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The results show that nuclear Kv1.3 channel binds to the UBF1 transcription factor, which participates in RNA polymerase I activity, mediating ribosomal RNA synthesis. It was reported that the NR1 subunit of the N-methyl-D-aspartate receptor was found in the nucleoli of hydra cells, which could serve as a regulator for ribosomal subunit production (47). Therefore, nuclear Kv1.3 channels appear to play the role of regulators in ribosome biogenesis, although this possibility needs to be studied further.…”
Section: Discussionmentioning
confidence: 96%
“…The results show that nuclear Kv1.3 channel binds to the UBF1 transcription factor, which participates in RNA polymerase I activity, mediating ribosomal RNA synthesis. It was reported that the NR1 subunit of the N-methyl-D-aspartate receptor was found in the nucleoli of hydra cells, which could serve as a regulator for ribosomal subunit production (47). Therefore, nuclear Kv1.3 channels appear to play the role of regulators in ribosome biogenesis, although this possibility needs to be studied further.…”
Section: Discussionmentioning
confidence: 96%
“…1. The putative NLS and/or nucleolar localization sequences (NoLS) located in cassette 1 of the GluN1 subunit has two short regions rich in basic amino acids, which comprise the NLS and are potentially involved in nucleolar signaling [66,67]. GluN1 subunits are tightly subjected to multiple levels of regulation, affecting subunit expression, subcellular location, and assembly of functional receptors, and their signaling complexes [34].…”
Section: Roles and Potential Fates Of Glun1 Subunit In The Cellular N...mentioning
confidence: 99%
“…DNA methylation, p53 activation, and post-transcriptional histone deacetylase are processes in the chromatin [86]. The GluN subunit has roles in cellular development and communication, reflecting dynamic cell retraction [34,67]. Early-life stress is a potent risk factor for the development of chronic pain, although the underlying mechanisms remain poorly understood.…”
Section: Epigenetic Influence On Glun1 Subunit In Nuclear Organellesmentioning
confidence: 99%
“…NO enters the presynaptic membrane, which causes the phosphorylation of protein, the influx of Ca 2+ and the glycosylation of protein kinase C. It then activates the expression of some early immediate genes (c-fos and c-jun) and transcription factors (CREB). The transcription factors change the expression of nuclear genes, including the subunit gene of NMDARs, and ultimately cause the synthesis of different proteins [30][31][32] .…”
Section: Abnormality Of the Nmdar-psd95-camkii Pathway May Contributementioning
confidence: 99%